2013
DOI: 10.1080/14693062.2013.823334
|View full text |Cite
|
Sign up to set email alerts
|

Developing country perspectives on ‘mitigation actions’, ‘NAMAs’, and ‘LCDS’

Abstract: The MAPS programme, which seeks to deepen mitigation ambition in developing countries, is engaged in exploring the concepts of Nationally Appropriate Mitigation Actions (NAMAs) and Low Carbon Development Strategies (LCDS) from a developing country perspective. Here, climate mitigation practitioners in six developing countries were surveyed for their understanding of these concepts (anonymous, personal communications with climate mitigation practitioners in Argentina, Brazil, Chile, Colombia, India, and South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 1 publication
(1 reference statement)
0
29
0
Order By: Relevance
“…As a result, the scope and aims of NAMAs vary considerably [4]. A study by Tyler et al [6] revealed that NAMAs are widely interpreted by policy makers in developing countries as mitigation activities packaged for submission to the UNFCCC registry. However, they are not held to constitute the full set of mitigation activities in a developing country.…”
Section: Experience With the Development And Implementation Of Leds Amentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, the scope and aims of NAMAs vary considerably [4]. A study by Tyler et al [6] revealed that NAMAs are widely interpreted by policy makers in developing countries as mitigation activities packaged for submission to the UNFCCC registry. However, they are not held to constitute the full set of mitigation activities in a developing country.…”
Section: Experience With the Development And Implementation Of Leds Amentioning
confidence: 99%
“…The still-nascent nature of the concept is said to present an opportunity (with scope for flexibility, customization and innovation) for developing countries to shape NAMAs to their benefit and take action appropriate to locally-required development [4,5]. Notwithstanding the conceptual uncertainties regarding NAMA (due to the complexity of the issue and the slow nature of negotiations [4]), it is considered to be the only existing operational concept with which the international process might raise mitigation ambitions [4,6]. Moreover, in terms of reporting, the introduction of NAMAs is said to have increased the frequency and breadth of the requirements for developing countries [4].…”
Section: Experience With the Development And Implementation Of Leds Amentioning
confidence: 99%
See 3 more Smart Citations